Cell Senescence-Related Pathways Are Enriched in Breast Cancer Patients With Late Toxicity After Radiotherapy and Low Radiation-Induced Lymphocyte Apoptosis - Aguado-Flor, Ester; Fuentes-Raspall, María J.; Gonzalo, Ricardo; Alonso, Carmen; Ramón y Cajal, Teresa; Fisas, David; Seoane, Alejandro; Sánchez-Pla, Álex; Giralt, Jordi; Díez, Orland; Gutiérrez-Enríquez, Sara (Frontiers in Oncology, 2022)
Background: Radiation-induced late effects are a common cause of morbidity amongst cancer survivors. The biomarker with the best evidence as predictive test of late reactions is the radiation-induced lymphocyte apoptosis (RILA) assay. We aimed to investigate the molecular basis underlying the distinctive RILA levels by using gene expression analysis in patients with and without late effects and in whom we had also first identified differences in RILA levels. Patients and methods: Peripheral blood mononuclear cells of 10 patients with late severe skin complications and 10 patients without symptoms, selected from those receiving radiotherapy from 1993 to 2007, were mock-irradiated or irradiated with 8 Gy. The 48h response was analysed in parallel by RILA assay and gene expression profiling with Affymetrix microarrays. Irradiated and non-irradiated gene expression profiles were compared between both groups. Gene set enrichment analysis was performed to identify differentially expressed biological processes. Results: Although differentially expressed mRNAs did not reach a significant adjusted p-value between patients suffering and not suffering clinical toxicity, the enriched pathways indicated significant differences between the two groups, either in irradiated or non-irradiated cells. In basal conditions, the main differentially expressed pathways between toxicity and non-toxicity groups were transport of small molecules, interferon signalling and transcription. After 8 Gy, the differences lied in pathways highly related to cell senescence like cell cycle/NF-kB, G-protein-coupled receptors and interferon signalling. Conclusion: Patients at risk of developing late toxicity have a distinctive pathway signature driven by a deregulation of immune and cell cycle pathways related to senescence, which in turn may underlie their low RILA phenotype.